Artificial Intelligence in Physical Education: A Systematic Review of Personalized Learning, Assessment, and Performance Analytics - Robyn Webber; Kymberly Starks; M. M. Williams; Berislav Ćosić's (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. This systematic review examines how artificial intelligence (AI) is applied to personalized learning, assessment, and performance analytics in physical education (PE) across K–12 and higher-education settings, with the aim of synthesizing empirical evidence, identifying patterns of implementation, and proposing evidence-based directions for future research and practice. Materials and methods. A systematic review was conducted following the PRISMA 2020 guidelines. Seven electronic databases (Web of Science, Scopus, EBSCOhost, PubMed, ACM Digital Library, Taylor & Francis Online, and Wiley Online Library) were searched from January 2014 to December 2025, using a reproducible Boolean search string centered on